2022
DOI: 10.46576/wdw.v16i1.1772
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Guru Pamong Terhadap Keterampilan Dasar Mengajar Mahasiswa Magang Tiga Di Sma Swasta Santu Xaverius Gunungsitoli Tahun Pelajaran 2020/2021

Abstract: This study aims to: (1) knowing the perception of the civil servant teacher on the basic skills of teaching three apprentice students. ( 2) fiind some basic teaching skills that must be possessed by interns in helping the success of the teaching process in the classroom. ( 3) knowing the efforts given by the civil servant teacher to overcome weaknesses in mastering basic teaching skills.. The results showed that: (1) basic teaching skills taught to students help in carrying out learning activities. ( 2) There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other findings also confirm that family factors, such as educational background, employment, and parental support, have contributed significantly to children's educational performance at school (Ratnawati, 2016;Rosikum, 2018;Yoga Purandina & Astra Winaya, 2020). Previous research findings also state that individuals need to actively develop the ability to adapt to work by participating in internship participation experiences; through this program, there is a balance between classroom teaching and the development of practical skills in the world of work (Gohae, 2020;Lase, 2022;Samidjo, 2017). It was concluded that Perceptions of Productive Competence, Internships, and Family Support will influence vocational school students' work readiness.…”
Section: Introductionmentioning
confidence: 57%
“…Other findings also confirm that family factors, such as educational background, employment, and parental support, have contributed significantly to children's educational performance at school (Ratnawati, 2016;Rosikum, 2018;Yoga Purandina & Astra Winaya, 2020). Previous research findings also state that individuals need to actively develop the ability to adapt to work by participating in internship participation experiences; through this program, there is a balance between classroom teaching and the development of practical skills in the world of work (Gohae, 2020;Lase, 2022;Samidjo, 2017). It was concluded that Perceptions of Productive Competence, Internships, and Family Support will influence vocational school students' work readiness.…”
Section: Introductionmentioning
confidence: 57%
“…Mastery of teaching skills must be intact and integrated so that systematic training is needed to create creative, professional, and fun learning (Mulyasa, 2015). Teaching skills (teaching skills) are competencies and skills that must be possessed by a teacher to be able to carry out learning practically and run smoothly (Fatiani Lase, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of development for developers in the world of higher education, especially in educational institutions, is a foothold or reference as an effort to improve systems, situations, and products in the hope that it can have implications for knowledge and skills for civil service teachers in guiding practical students (Lase, 2022;Rhamayanti, 2018). Development is an activity that boils down to a result or product (Hendi et al, 2020;Kurniawan et al, 2020;Puspita., 2019).…”
Section: Introductionmentioning
confidence: 99%